MIRROR OF SENSITIVITY BETWEEN RECEIVING AND SPECIAL EDUCATION TEACHER IN REGULAR EDUCATION TOWARD INCLUSION (Proceedings of International Conference on Special Education, 2019)
Inclusion of special education students in the regular education setting is a very complex and interesting topic in education. Often times it is at the center of debate amongst administrators, teachers, and parents. Each person has their own ideas and attitudes about what is best for all children. Multiple research studies have revealed that there are many different factors for positive and negative teacher attitudes toward inclusion. This study examined and analyzed receiving teacher in regular education and special education teacher attitudes toward inclusion. This research also assessed on the profile variables such as position, years of teaching experience and subjects handled. Descriptive analysis method of research was used since questionnaires served as the major instrument in analyzing the data. Results of the survey were tabulated with frequencies and percentages for each response reported and for more in-depth analysis and interpretation correlation was applied. Interview was randomly administered to validate responses and gather enough evidence to test the null hypothesis for rejection or acceptance. The results of this study indicated the positive and negative attitudes of special education teachers and receiving teachers in regular education about inclusion. The results revealed some significant relationships in attitudes reported by receiving teacher in regular education and special education teachers. The results of this study also identified possible factors behind the teacher attitudes on inclusion.